Mata dan Manusia Laut Karya Okky Madasari: Tinjauan Ekokritik Greg Garrard - Juanda, Juanda (Universitas Suryakanca, 2025)
This article explores the representation of human and environmental relationships in Okky Madasari's novel “Mata dan Manusia Laut” using Greg Garrard's ecocritical approach. This theoretical framework has six main aspects: pollution, wilderness, disaster, settlement, animals, and the earth. This research method is qualitative with a descriptive-analytical approach. The data comes from direct quotations in the text that represent environmental issues. Data analysis was conducted using NVivo software. The results of data analysis show that this novel voices criticism of the damage to marine and coastal ecology due to human activities, as well as the importance of ecological awareness through the main character, Mata, and her interactions with nature and the Bajo tribe. The novel not only conveys a moral message about environmental conservation but also raises the social inequality experienced by indigenous coastal communities facing modernization and exploitation. The most dominant aspect is pollution, with a coverage of 14.68%, indicating the high representation of environmental damage due to waste, marine pollution, and unsustainable human activities in the novel's narrative. The contribution of the research provides input to the government to make rules on environmental conservation that are pro-coastal people. Future research is the curriculum content of literature teaching materials on environmental themes. Keywords: ecocriticism; Greg Garrard; environment; humans and nature Abstrak Artikel ini mengeksplorasi representasi hubungan manusia dan lingkungan dalam novel “Mata dan Manusia Laut” karya Okky Madasari dengan pendekatan ekokritik Greg Garrard. Kerangka teori ini, terdapat enam aspek utama, yaitu: polusi, hutan belantara, bencana, pemukiman, binatang, dan bumi. Metode penelitian ini bersifat kualitatif dengan pendekatan deskriptif-analitis. Data bersumber dari kutipan-kutipan langsung dalam teks yang merepresentasikan isu-isu lingkungan. Analisis data menggunakan software nvivo. Hasil analisis data menunjukkan bahwa novel ini menyuarakan kritik terhadap kerusakan ekologi laut dan pesisir akibat ulah manusia, serta pentingnya kesadaran ekologis melalui tokoh utama, Mata, dan interaksinya dengan alam serta masyarakat suku Bajo. Novel ini tidak hanya menyampaikan pesan moral tentang pelestarian lingkungan, tetapi mengangkat ketimpangan sosial yang dialami masyarakat adat pesisir menghadapi modernisasi dan eksploitasi. Aspek yang paling dominan adalah polusi, dengan cakupan sebesar 14,68% yang menandakan tingginya representasi kerusakan lingkungan akibat limbah, pencemaran laut, dan aktivitas manusia yang tidak berkelanjutan dalam narasi novel. Kontribusi penelitian memberikan masukan kepada pemerintah untuk membuat aturan tentang pelestarian lingkungan yang pro pada rakyat pesisir. Penelitian ke depan adalah muatan kurikulum materi pengajaran sastra tema lingkungan. Katakunci: ekokritik; Greg Garrard; lingkungan; manusia dan alam